Orthotopic Liver Transplantation in a Case of Novel YAP1-TFE3 Hepatic Epithelioid Hemangioendothelioma [HEHE]; Case Report and Review of Literature (Journal of Renal and Hepatic Disorders, 2021)
Epithelioid hemangioendothelioma is an extremely rare vascular neoplasm arising in soft-tissues and different visceral organs, with liver being the most commonly involved viscera. Hepatic epithelioid hemangioendothelioma (HEHE) is a malignant tumour with an indolent behaviour and unpredictable clinical course. It has a better prognosis among the malignant tumours of the liver, in spite of being a diffuse multifocal liver disease or metastatic at the time of presentation. HEHE is usually found to be noted in the fifth decade with slight female preponderance. No single treatment strategy has yet been established owing to its variable clinical course, ranging from an indolent tumour with prolonged survival to an aggressive, metastatic disease with a fatal outcome. Here, we present a case of a novel HEHE in a 25-year-old female who was treated successfully with orthotopic living donor liver transplantation and discuss the presentation, histopathology and management of this rare, fatal yet treatable malignant tumour.
Keywords: hepatic epitheloid hemangioendothelioma; vascular tumour